Avrupa Parlamentosu'nun Sırbistan'ın üyeliğine yönelik tartışmalarında kültürün yeri - Ağaoğlu, Neslihan Başak (My University, 2019)
Tezde, Avrupa Birliği’ne üyelik sürecinde Sırbistan’ın Avrupa Parlamentosu’nda yapılan tartışmalarda parlamenterler tarafından kültür bağlamında ele alınıp alınmadığı araştırılmıştır. Doğu olarak adlandırılan Balkanlardan en zorlu aday ülke olan Sırbistan’a yönelik Avrupa Parlamentosu’ndaki tartışmalar incelenmiştir. Aslında bunlar, Avrupa Birliği ülkelerinin vatandaşları tarafından seçilen parlamenterlerin söylemleridir. Tezde, Avrupa Birliği temelli Avrupalılık fikrini anlamak için sosyal inşacılık teorisi esas alınmıştır. Bu bakımdan Avrupa kültürü ve kimliği kavramlarının, Sırbistan’ın üyelik sürecine dair Avrupa Parlamentosu’nda yapılan tartışmalarda hangi değerlere atıf yapılarak ele alındığı ortaya konmuştur. Bunu anlayabilmek için de Sırbistan için hazırlanan ilerleme raporlarının Avrupa Parlamentosu’nda nasıl tartışıldığı, resmi belgelere ulaşılarak incelenmiştir. Buna göre, Sırbistan için hazırlanan ilerleme raporlarında genellikle hukukun üstünlüğü, demokrasi, insanlar haklarına saygı ve bölgesel işbirliği konularına değinilmektedir. Bölgesel işbirliği, Avrupa Birliği Antlaşması’nın 2.maddesinde yer alan değerlerden olmamasına rağmen, Avrupa Birliği’nin temel amacı olan Avrupa barışı, bölgesel işbirliği sayesinde mümkün olacaktır. Tez çalışması sırasında 2012 ve 2016 yılları arasında Avrupa Parlamentosu’nda yapılan tartışmalardan toplam 227 konuşma incelenmiştir. Buna göre bu tez, Avrupa Parlamentosu ile ilgili daha önce incelenmeyen bir alana açıklık getirmiştir.

In this thesis, Serbia’s membership process was discussed in the context of culture by parliamentarians in the European Parliament’s debates. Debates in the European Parliament for Serbia, which is the most challenging candidate country of the Balkans, are examined. In fact, these are the statements of the parliamentarians elected by the citizens of the European Union countries. The thesis was based on the theory of social constructivism to understand the idea of European Union-based Europeanism. In this respect, it was revealed that the concepts of European culture and identity were handled by referring to which values in the discussions held in the European Parliament about Serbia's membership process. In this context, this thesis has examined the concepts of European culture and identity from the constructivist point of view and this thesis also showed what values are referred to Serbia’s membership process. In order to understand how the progress reports for Serbia were discussed in the European Parliament, official documents were examined. According to this, the progress reports have generally addresssed the rule of law, democracy, respect for human rights and regional cooperation. Although regional cooperation is not one of the values contained in the Article 2 of the Treaty of European Union, European peace which is the main aim of the European Union, will be possible through regional cooperation. During the thesis study, a total of 227 speeches were discussed between the 2012 and 2016 in the discussions held in the European Parliament, and accordingly, this thesis clarified an area that had not been examined before concerning the European Parliament.
Keywords: Avrupa Birliği; Avrupa Parlamentosu; Batı Balkanlar European Union; Culture; European Parliament; European Union; Identity; Kimlik; Kültür; Serbia; Sırbistan; Western Balkans